Financing transportation networks - Levinson, David M. 1967- (E. Elgar Pub, 2002)
1. Introduction -- 2. History -- 3. Costs -- 4. Revenues -- 5. Hierarchy -- 6. Intertemporal equity -- 7. Finance choice on a beltway -- 8. Finance choice on an interstate -- 9. Finance choice at a frontier -- 10. Congestion pricing -- 11. Compensation -- 12. Deploying electronic tolls -- 13. Summary and conclusions
Includes bibliographical references (p. 215-227) and index
Keywords: Electronic books; Toll roads; Roads -- Finance